Arab Express: The Latest Art from the Arab World (Mori Art Museum; Heibonsha, Tokyo, 2013)
Exhibition catalog. Jun-Oct 2012. Curator: Fumio Nanjo
English; Japanese
Keywords: N4390-5098 Visual Arts- Exhibitions